2021
DOI: 10.3389/fcimb.2021.774537
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Naturally Acquired Immunity to a Panel of Antigens Expressed in Mature P. falciparum Gametocytes

Abstract: IntroductionNaturally acquired immune responses against antigens expressed on the surface of mature gametocytes develop in individuals living in malaria-endemic areas. Evidence suggests that such anti-gametocyte immunity can block the development of the parasite in the mosquito, thus playing a role in interrupting transmission. A better comprehension of naturally acquired immunity to these gametocyte antigens can aid the development of transmission-blocking vaccines and improve our understanding of the human i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…Although the specific function of Pf3D7_1314500 needs be further investigated, this predicted function in protein transport makes it unlikely that this antigen is a promising TBV candidate. However, a recent study showed that increased antibody responses to Pf3D7_1314500 in two cohorts of malaria-exposed individuals were significantly associated with gametocytemia, demonstrating a potential role as biomarker of gametocyte carriage ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the specific function of Pf3D7_1314500 needs be further investigated, this predicted function in protein transport makes it unlikely that this antigen is a promising TBV candidate. However, a recent study showed that increased antibody responses to Pf3D7_1314500 in two cohorts of malaria-exposed individuals were significantly associated with gametocytemia, demonstrating a potential role as biomarker of gametocyte carriage ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Muthui et al. set out to analyse naturally acquired antibody responses to seven antigens selected based on potential gametocyte surface expression, including Pfs230, PfMDV1 and five previously uncharacterized gametocyte antigens ( 49 ). They demonstrated antibody responses to all seven antigens, and suggested that PF3D7_0303900, PF3D7_1314500, and PF3D7_0208800 may have potential as markers of high gametocytaemia.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, cell free systems have been used to express multiple antigens for high-throughput screening of patient sera against an array of antigens. Such studies have shown that antibodies against Pf38 have an intermediate association with protection against symptomatic malaria ( Richards et al., 2013 ) and antibody levels against Pfs230C may be associated with age ( Muthui et al., 2021 ). Unfortunately, not all antigens appear to be amenable to expression via this system, with production of recombinant Pfs48/45, Pfs47 and PfPSOP12 proving unsuccessful ( Muthui et al., 2021 ).…”
Section: Expression Of Recombinant 6-cysteine Proteinsmentioning
confidence: 99%
“…Such studies have shown that antibodies against Pf38 have an intermediate association with protection against symptomatic malaria ( Richards et al., 2013 ) and antibody levels against Pfs230C may be associated with age ( Muthui et al., 2021 ). Unfortunately, not all antigens appear to be amenable to expression via this system, with production of recombinant Pfs48/45, Pfs47 and PfPSOP12 proving unsuccessful ( Muthui et al., 2021 ). This system has also been used to produce multiple vaccine candidates for functional comparison, supporting the further development of Pfs230C as a vaccine candidate ( Miura et al., 2013 ).…”
Section: Expression Of Recombinant 6-cysteine Proteinsmentioning
confidence: 99%